Two Unconventional Precursors to Produce ZnCl2-Based Activated Carbon for Water Treatment Applications - Cruz G.J.F. (2018)
The Academy of Sciences of the Czech Republic and Consejo Nacional de Ciencia, Tecnologia e Innovación Tecno-lógica (CONCYTEC) in Peru (joint project reg. No. 002/PE/ 2012) are gratefully recognized for their support.